Design and optimization of bonded patch repairs of laminated composite structures. (May 2015) - Gong, Xiao-Jing; Cheng, Pengcheng; Aivazzadeh, Shahram; Xiao, Xinran
Abstract: The present study proposes a method for design optimization of external patched repairs. The tensile behavior of notched specimens with patched repair was studied using finite element analysis and compared with experimental results. It was found that high stress concentrations along the transverse edges of circular patches and/or at the longitudinal edges of the hole leads to early damage initiation in the parent plate. The damage initiation site and its propagation depend on the patch in-plane stiffness. The optimal patch design can be characterized by a strength ratio R ∗ . The overall design of the patch repair can be considered using a dimensionless design parameter K .